If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 + 4g = 33 Solving -27 + 4g = 33 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 4g = 33 + 27 Combine like terms: -27 + 27 = 0 0 + 4g = 33 + 27 4g = 33 + 27 Combine like terms: 33 + 27 = 60 4g = 60 Divide each side by '4'. g = 15 Simplifying g = 15
| 15x^2+123x-108=0 | | 18m=6m | | 2x^3-17x=0 | | 3-2x=x^2+3x-3 | | 4x+5=2x-8 | | 5k^3-26k^2+24k=0 | | 2x^3-17=0 | | x+(x-1)=55 | | 74=4+2b | | ln(3x+6)=7 | | 3(4x-1)=6 | | 6y=3x+2 | | 30x-(-x+6)+(-5x+4)=-(5x+6)+(-8+30) | | X^2+4x-y-6=0 | | (2cos^2x-1)-cosx=0 | | 24b=6b | | 20*8= | | X+6(x+2)=3x-4 | | -8x+(-5x)=x | | (3k+2)(3k+2)=49 | | x^2+25x-4344=0 | | 2x^3y^3+3x^2y^2+4y=0 | | 10+4(-3)=x | | (7x-11)(3x-8)=0 | | 2/3+a-5/9=-a+2a | | X^2+y^2-10x-4y+20=0 | | 5-15s=8-16s | | 10-(-10)=x | | 3(v+2)+2v=7(v+1)+9 | | 6x+41+4x+39=180 | | x+y+14x-12y+4=0 | | x^2+19x+12=0 |